PEMBELAJARAN BERBASIS PADA MASALAH DALAM MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH MATEMATIKA - Prayitno, Anton; Rina, Rina (Jurnal Likhitaprajna, 2019)
This mix method research was conducted for seventh grade students at Nurul Huda Poncokusomo Islamic Middle School, East Java. The purpose of this study was to investigate and analyze the role of teachers in problem-based learning. The research instruments are worksheets, observations, and tests. Each worksheet contains 2 math problems and 2 test questions. This learning is carried out in two learning sessions. The results show that there is an increase in students' ability to solve problems about the set, both given on worksheets or tests. The problem-based learning steps help students to investigate either in groups or independently. Besides that, this learning can improve students' understanding so that they are able to solve problems about the set. Another increase was shown by the existence of teachers and lecturers in organizing and guiding students by involving students in real situations.Keyword: problem-based learning, set, collaborative learning